Corporate Criminal Liability in Environmental Crimes (a Case Study) - Hyronimus Rhiti (Gudang Jurnal Multidisiplin Ilmu, 2023)
Crimes against the environment in the form of environmental destruction can be committed by individuals or corporations. Business activities carried out by corporations often cause environmental damage, because corporate activities are primarily aimed at profit. This article was written using a normative legal research method with a case approach. The legal materials used in writing this article are primary legal materials and secondary legal materials. The results of this research are criminal liability for corporations that commit criminal acts as in Decision Number No. 133/Pid.B/2013/PN. Mbo is in the form of civil lawsuit sanctions for losses suffered by victims and criminal sanctions.